Pengembangan E-LKPD Berbantuan Audiovisual dengan Cover Education Song pada Materi Sistem Rangka di Kelas XI - Sibarani, Febi Christina; Citrawathi, Desak Made; Heny , Ajeng Purnama (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This development study aims to produce E-LKPD with audiovisual-based cover education songs on the skeletal system material for grade XI senior high school that is valid and practical for use in learning. The development model applied is 4D (Four-D) by Thiagarajan (1974), which includes the Define, Design, Develop, and Disseminate stages. The research was conducted at Kubutambahan 1 Senior High School. The validity test was carried out using Gregory's formula, involving two subject matter experts and two media experts. The assessment results showed that the Gregory Validity Coefficient (GVC) of both subject matter and media experts scored 1, which is classified as highly valid. Furthermore, the practicality test involved three biology teachers and 31 grade XI students at Kubutambahan 1 Senior High School. The assessment results showed a practicality level of 91.42% from teachers and 84.51% from students, both of which were classified as highly practical. Thus, the E-LKPD E-LKPD with audiovisual-based cover education songs on the skeletal system material for grade XI senior high school was declared highly valid and highly practical to support the learning process in grade XI senior high school.